Increasing Latinx representation in the US medical schools: A top-ranked medical school's experience - Corsino, Leonor; Chinea, Félix M.; Yee, Linton; Fuller, Anthony T. (Frontiers in Public Health, 2022)
Despite the increasing racial and ethnic diversity of the general US population, many, if not most, medical schools fall short of matriculating students reflective of this change in diversity. The Latinx community constitutes nearly 20% of the US population and is expected to rise substantially in the coming decades. Over the past 20 years, the number of Latinx students applying to and being admitted to medical school has grown but remains below 4% of the total medical student body composition. Several factors contribute to the under-representation of Latinx students in medical schools that include access to secondary education, finances, lack of mentorship or advice, and a multitude of other structural inequities and system-level biases. Diversity, equity, and inclusion are often named as key pillars of workforce development across the US medical schools and academic institutions. Despite significant efforts, medical schools continue to have low Latinx representation within their student body, and recruitment efforts often lack sustainability. In this manuscript, we share our experience of increasing Latinx student representation within a top-ranked medical school in the US southeast region. We have discussed the barriers we faced in enrolling and attracting Latinx students' amidst similar under-representation of Latinx faculty, staff, and leadership and the challenges of financial support for applicants and financial aid packages for admitted students. The strategies we implemented to achieve an increased representation of Latinx students in the School of Medicine (SOM) included revitalizing the Latino Medical Student Association (LMSA), ensuring Latinx student representation within the SOM admission committee that included Latinx faculty as active participants in recruitment and retention efforts, redesigning the medical Spanish course, and creating dedicated outreach plans during second look weekend for interested Latinx students and active outreach to applicants and accepted students by current students. In combination, these efforts led to a significant increase in Latinx representation in the SOM student body from 2.6% in 2009 to 12.2% in 2021. We will conclude by discussing our ongoing challenges and our approach to sustain and improve Latinx representation in our medical school.